PELATIHAN TRAINING OF TRAINER (TOT) DIGITAL PUBLIC RELATION DALAM UPAYA MENINGKATKAN KUALITAS HUBUNGAN MASYARAKAT DI LEMBAGA - M Arief Rahman; Alem Pameli; Yulia Hapsari; Leni Novianti; Eka Yuda Gunawibawa (PPPM POLTESA, 2023)
Training of Trainers (TOT) Digital Public Relations (DPR) aims to improve the quality of public relations in institutions. The digital age has changed the way we communicate and interact, thus making Digital PR very important. TOT Digital PR provides PR practitioners with the understanding and skills to operate in a digital environment. The program also focused on developing instructional skills. The results of this training successfully provided participants with the ability to manage public relations in the digital era. The training encouraged the improvement of institutional public relations and the use of DPR for more effective communication. As such, TOT DPR assists institutions in utilizing more competent human resources in the ever-evolving digital age.